Dorothy Day : Love in Action - Jordan, Patrick (Book collections on Project MUSE., 2015)
By any measure, Dorothy Day lived a fascinating life. She was a journalist, activist, single mother, convert, Catholic laywoman, and co-founder of the Catholic Worker Movement. A lifelong radical who took the gospels at their word, Dorothy Day lived among the poor as one of them, challenging both church and state to build a better world for all people. Steeped in prayer, the liturgy, and the spiritual life, she was jailed repeatedly for protesting poverty, injustice, and war. Through it all, she created a sense of community and remained down-to-earth and humanly approachable. To have known Dorothy Day was to have experienced not only her charm and humanity, but the purposefulness of her life. In Dorothy Day: Love in Action, Patrick Jordan-who knew her personally-conveys some of the hallmarks of Day's fascinating life and the spirit her adventure inspires. People of God is a series of inspiring biographies for the general reader. Each volume offers a compelling and honest narrative of the life of an important twentieth or twenty-first century Catholic. Some living and some now deceased, each of these women and men has known challenges and weaknesses familiar to most of us but responded to them in ways that call us to our own forms of heroism. Each offers a credible and concrete witness of faith, hope, and love to people of our own day. -- Provided by publisher.